Residents’ self-perceived health and its relationships with urban neighborhood green infrastructure - Mansor, Mazlina; Harun, Nor Zalina; Zakariya, Khalilah (Elsevier, 2015)
Research has established that being in green elements in the landscape affect health and well-being. This paper presents the findings whether neighborhood green infrastructure (GI) in a community’s living environment is an underlying mechanism for urban residents’ self-perceived health. To study this, we seek residents’ participations through their responses, in which we investigated: (a) residents’ inputs in the ways they use and perceive GI near their homes, and (b) the residents’ self-perceived health based on their reported status of health. When an association between the GI and self-perceived health was found, we analyzed whether this could explain the relationship between the two parameters. The results are important in addressing the relationship of GI with respondents’ health status. 650 residents living in Bandar Tun Razak town responded to the survey questionnaires. Bandar Tun Razak is one of the established towns within the periphery of Kuala Lumpur. The analyses suggest that residents frequently spent time in Taman Tasik Permaisuri (a recreational park), their home gardens and in open spaces in their neighborhoods. The research also found that there is an association between GI with their self-perceived health. This finding can be translated into policy on health promotion in Malaysia through landscape design and planning of urban green spaces. The study is also relevant for multi-disciplinary fields of study such as urban planning and public health promotion.